1986
DOI: 10.1161/01.cir.73.3.484
|View full text |Cite
|
Sign up to set email alerts
|

Internal cardiac defibrillation in man: pronounced improvement with sequential pulse delivery to two different lead orientations.

Abstract: Wider applicability of an implantable automatic defibrillator depends on achieving internal cardiac defibrillation consistently with the lowest possible energy. In animal studies, we have found that the cardiac defibrillation threshold could be reduced when sequential shocks separated in time and spacially arranged were delivered to the heart. We compared internal cardiac defibrillation using a single pulse shock delivered through an intravascular catheter with this new method for internal cardiac defibrillati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(21 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…The size of output capacitors is constrained by the combined requirements to store sufficient energy to defibrillate reliably and to operate below voltages at which components of the output circuit fail or myocardial damage occurs.10,262829 The output circuits of current pulse generators can operate safely at voltages over 1000 V.1 10 There is substantial reason to believe that voltages higher than 750 V (corresponding to 34 J from a 120-,F capacitor) may be safe. During defibrillator implantation, internal 815-V (40 J) rescue shocks are given routinely, pulses up to 1000 V have been shown to be safe in dogs,30 and humans have been defibrillated safely with voltages up to 1420 V. 31 In the present study, we detected no adverse effects from 910-V pulses (25 J from 60-,uF capacitors). However, additional safety studies are required before voltages greater than 750 V can be recommended for implanted pulse generators.…”
Section: Comparison With Previous Studiessupporting
confidence: 50%
“…The size of output capacitors is constrained by the combined requirements to store sufficient energy to defibrillate reliably and to operate below voltages at which components of the output circuit fail or myocardial damage occurs.10,262829 The output circuits of current pulse generators can operate safely at voltages over 1000 V.1 10 There is substantial reason to believe that voltages higher than 750 V (corresponding to 34 J from a 120-,F capacitor) may be safe. During defibrillator implantation, internal 815-V (40 J) rescue shocks are given routinely, pulses up to 1000 V have been shown to be safe in dogs,30 and humans have been defibrillated safely with voltages up to 1420 V. 31 In the present study, we detected no adverse effects from 910-V pulses (25 J from 60-,uF capacitors). However, additional safety studies are required before voltages greater than 750 V can be recommended for implanted pulse generators.…”
Section: Comparison With Previous Studiessupporting
confidence: 50%
“…Prior studies also showed sequential shock schemes can produce lower DFTs than single shock schemes, but none placed a lead transvenously on the middle of the LV free wall. 12,13 Animal and clinical studies demonstrated substantial reductions in DFT using a small epicardial patch on the LV free wall and a sequential shock waveform, but this approach is no longer clinically acceptable due to the need for transthoracic patch insertion. 3,13 Other sequential shock studies used small, temporary defibrillation catheters that bear little resemblance to modern ICD leads, and most studies used 2 monophasic shocks delivered with equal amplitudes.…”
Section: Prior Studiesmentioning
confidence: 99%
“…12,13 Animal and clinical studies demonstrated substantial reductions in DFT using a small epicardial patch on the LV free wall and a sequential shock waveform, but this approach is no longer clinically acceptable due to the need for transthoracic patch insertion. 3,13 Other sequential shock studies used small, temporary defibrillation catheters that bear little resemblance to modern ICD leads, and most studies used 2 monophasic shocks delivered with equal amplitudes. 12 The present study bears closest resemblance to that of Exner et al, 14 who reported a 44% reduction in DFT with sequential biphasic waveforms.…”
Section: Prior Studiesmentioning
confidence: 99%
“…Energy was calculated by the integrated area under the curve and the correction for the logarithmic decay of the capacitive discharge. 4 Although the value for the mean defibrillation threshold of the group receiving test shocks greater than 2.25 times defibrillation threshold was the lowest, there was no statistical difference between the groups (F= 2.01 at 4 and 44 df, p>0.05) of the 51 patients, 50 of whom were undergoing surgical ablation of the accessory pathway for Wolff-ParkinsonWhite syndrome. The additional patient was having an internal defibrillator implanted.…”
Section: Energy Delivery Determinationmentioning
confidence: 86%
“…Defibrillation threshold was defined as the minimum energy required to cause defibrillation. 4 Once defibrillation threshold had been determined, estimated stored voltage for a test shock was calculated, which would correspond to that necessary to deliver the randomly selected ratio of defibrillation threshold energy for that patient. The initial stored voltage was set at the test shock voltage level.…”
mentioning
confidence: 99%